Investigation and application of diffusive gradients in thin-films technique for measuring endocrine disrupting chemicals in seawaters. (June 2018) - Xie, Huaijun; Chen, Qining; Chen, Jingwen; Chen, Chang-Er L.; Du, Juan
Abstract: Endocrine disrupting chemicals (EDCs) can be released to coastal waters and affect the endocrine system of marine organisms. To monitor their levels in seawaters, a simple, robust passive sampling method, the diffusive gradients in thin-films (DGT) technique, was developed with XDA-1 resin as a binding agent. Six EDCs (including three estrogens, two pesticides and bisphenol A) were used to assess the performance of the DGT. The XDA-1 binding gel showed adequate ability for adsorbing EDCs in seawaters. The DGT sampler exhibited linear accumulation for the EDCs during a 15-day deployment and diffusion coefficients and sampling rates were calculated. The DGT measurement was independent of pH in the range 7.0–9.0 and ionic strength in the range 0.4–0.8 M. Field applications of this DGT in a coast of Dalian (China) showed comparable results to those from grab sampling. Five EDCs were detected with concentrations ranging from 0.7 to 19.4 ng L −1 . This study is a first attempt to apply DGT sampler for determining EDCs in seawaters. Highlights: XDA-DGT was developed for determining EDCs in seawaters. XDA-DGT is suitable for a range of pH (7–9) and ionic strength (0.4–0.8 M). XDA-DGT showed good linear uptakes for EDCs over 15 d in artificial seawater.